The moderating effect of distinctive capabilities on the competitive strategy and performance relationship in Malaysian SMEs / Mohd Khairuddin Hashim ... [et al.] - Hashim, Mohd Khairuddin; Wafa, Syed Azizi; Mohamad, Osman; Sulaiman, Mohamad (Faculty of Business and Management ; UiTM Press, 2002)
Although distinctive capabilities are crucial to the success of firms, few studies have focused on this strategic variable, particularly in small and medium enterprises (SMEs). Furthermore, previous empirical studies have neglected to consider distinctive capabilities as having moderating effect on the competitive strategy-performance linkage. The purpose of this study is to address this issue. Based on a sample survey of 100 SMEs operating across Northern Malaysia, this study found significant differences in the mean growth in ROI, ROA, and the Business Performance Composite Index, among the SMEs that adopted different competitive strategies. The results also indicate that distinctive capabilities do moderate the relationship between competitive strategy and performance of SMEs.